HOLLOW DIRECT SUMMANDS OF THE DUAL AUTOMORPHISM-INVARIANT MODULES - Nadira Noer, Farah
A module is called an automorphism-invariant module if every isomorphism between its two essential submodules extends to an automorphism of its module. This thesis studies the dual of such modules, namely how to obtain its definition from the definition of automorphism-invariant module and investigates the examples followed by each characterization. If there are concepts about submodule and essential submodule in the definition of automorphism invariant module, then there will be concepts about factor module and small submodule in the definition of dual of such module. The examples of dual automorphism-invariant module are module over V -ring and pseudo-projective module. This thesis studies the structure of direct summands of dual automorphism-invariant module, particulary if its direct summands are hollow module.